Optimization of inoculum cell concentration for enhanced lipid production in laboratory-scale cultivation of the marine microalga Chlorella sp. for biofuel applications - Abdul-Sani, Erma Rizah; Chin, Grace Joy Wei Lie; Yong, Wilson Thau Lym; Misson, Mailin (Frontiers in Energy Research, 2024)
Microalgae are considered valuable bioresources due to their ability to produce high lipid content and grow under a variety of environmental conditions, making them strong candidates for sustainable biofuel production. However, the economic feasibility of microalgae-based biofuels depends on optimizing growth conditions in large-scale cultivation systems. This study investigates the effects of varying inoculum cell concentrations on the growth, lipid yield, and fatty acid composition of the locally isolated microalga Chlorella sp. SW5 in 2 L and 5 L cultivation systems. The results indicate that higher inoculum concentrations generally enhance biomass accumulation, with the 2 L system achieving the highest growth rate of 0.42 ± 0.01 day⁻¹ at an inoculum concentration of 10⁶ cells/ml. Interestingly, while higher inoculum concentrations reduced lipid production in the 2 L system, the 5 L system showed the highest lipid yield (51.23 ± 4.71% dry weight) at the highest inoculum concentration (10⁷ cells/ml). Despite its moderate growth rate, the 5 L culture with a starting inoculum concentration of 10⁷ cells/ml was selected for fatty acid profiling due to its superior lipid yield and productivity. Gas chromatography-mass spectrometry (GC-MS) analysis revealed that the culture produced a total of 93.18% C14-C18 fatty acids, with a profile dominated by saturated (56.33%) and monounsaturated (16.85%) fatty acids, which are essential for biodiesel quality. These findings provide valuable insights into the potential for scaling up microalgal systems for commercial biofuel production, highlighting strategies to optimize productivity.